2018
DOI: 10.1002/pc.25113
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance evaluation of polytetrafluoroethylene composites under dry sliding and aqueous environments using taguchi approach and grey relational analysis: Effect of material, test environment and load

Abstract: This study examined the friction and wear behavior of polytetrafluoroethylene composites filled with 25 wt% glass fiber, 25 wt% graphite and 60 wt% bronze under dry sliding conditions and under distilled water and sea water environments. Taguchi methodology was employed to plan experiments. The friction and wear experiments were conducted using a pin on disc tribometer at room temperature. Optimization of the chosen process variables (viz., material [M], test environment [E], and load [L]) for friction and wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Taguchi approach being simple and systematic is used to optimize parameters, which includes design for cost, quality, and performance. 42,48,49 Various industrial experts and researchers have adopted Taguchi approach effectively to optimize their experimental studies. [43][44][45]50,51 In Taguchi method, deviation between measured and desired values is obtained by employing a loss function, which is then converted to a signal-to-noise (S/N) ratio.…”
Section: Taguchi Approach For Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Taguchi approach being simple and systematic is used to optimize parameters, which includes design for cost, quality, and performance. 42,48,49 Various industrial experts and researchers have adopted Taguchi approach effectively to optimize their experimental studies. [43][44][45]50,51 In Taguchi method, deviation between measured and desired values is obtained by employing a loss function, which is then converted to a signal-to-noise (S/N) ratio.…”
Section: Taguchi Approach For Experimental Designmentioning
confidence: 99%
“…[39][40][41] In some research studies, it has also been revealed that the control factors can also be optimized during the development and characterization of composite materials using Taguchi approach to achieve the desired results. 39,42 Taguchi technique is one of the optimization methods, which has been used on a wide scale. In this technique, the design of experiments is used to analyze the significance of processing parameters affecting the performance of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, several prediction approaches are also used to predict and validate the experimental outcomes. [39,40,41,42] Jebran et al [43] have optimized the wear and friction behaviors of glass, bronze, and graphite-filled PTFE composite. The experiment was conducted by varying the sliding conditions and working environment, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The wear characteristics of 80 % silicon carbide + 20 % aluminum oxide hybrid metal matrix composite were varied depending on applied load and the relative ratio of silicon carbide and aluminum oxide [14]. Many researchers have used Taguchi based Grey relational analysis to optimize the multiple response characteristics [15][16][17][18][19][20]. In this work, an attempt has been to analyse the influence of reinforcement of titanium carbide and basalt in Al7075 on wear rate and coefficient of friction simultaneously using Grey-Taguchi method.…”
Section: Introductionmentioning
confidence: 99%